Effect of elevated O3 on rhizospheric enzymatic activities of ozone sensitive and tolerant wheat cultivars. Issue 12 (15th October 2018) - Fatima, Adeeb; Singh, Aditya Abha; Agrawal, Madhoolika; Agrawal, Shashi Bhushan
ABSTRACT: Tropospheric ozone (O3 ) is considered harmful to agriculture production and soil community. Wheat cultivars HD 2987 (O3 sensitive) and Kharchiya 65 (O3 tolerant) were grown under ambient and elevated (ambient + 30 ppb) levels of O3 (EO) using open top chambers, and microbial biomass and enzymatic activities were investigated in soil rhizosphere. Elevated O3 declined soil enzymatic activities related to carbon cycling viz. β-glucosidase, cellobiohydrolase, cellulase and amylase more in sensitive cultivar compared to tolerant. Enzymatic activities linked to nitrogen cycling like N-acetyl-glucosaminidase and urease decreased while protease and glycine aminopeptidase increased. Microbial biomass carbon and nitrogen declined more in sensitive cultivar by 11.1 and 21.2%, respectively. Root biomass reduced in wheat cultivars with an increase of their phenolics contents by 34.3 and 10.2% in HD 2987 and Kharchiya 65, respectively at 60 days after germination. Non-significant changes were observed in soil organic carbon and total nitrogen in both the cultivars. Redundancy analysis suggested that soil enzymatic activities were predominantly affected by O3 induced changes in microbial biomass carbon and root biomass. Study also showed that rhizosphere of sensitive cultivar HD 2987 was affected more under EO as compared to tolerant Kharchiya 65.